Answer:
x = 1
x = -9
Step-by-step explanation:
(2x2 + 16x) - 18 = 0
2x2 + 16x - 18 = 2 • (x2 + 8x - 9)
x2 + 8x - 9
-9 + 1 = -8
-3 + 3 = 0
-1 + 9 = 8
2 • (x + 9) • (x - 1) = 0
2 = 0
x+9 = 0
x = -9
x-1 = 0
x = 1
x2 + 8x - 9 = 0
x2+8x = 9
(x+4) • (x+4) =
(x+4)2
x2+8x+16 = 25 and
x2+8x+16 = (x+4)2
(x+4)2 = 25
x = -4 + √ 25
x2 + 8x - 9 = 0
has two solutions:
x = -4 + √ 25
or
x = -4 - √ 25
- B ± √ B2-4AC
x = ————————
2A
A = 1
B = 8
C = -9
B2 - 4AC =
64 - (-36) =
100
-8 ± √ 100
x = —————
2
x = ( -8 ± 10) / 2
x =(-8+√100)/2=-4+5= 1.000
or:
x =(-8-√100)/2=-4-5= -9.000
Answer: x = 1
x = -9
Here's your answer
c^2+7c-6
To get slope-intercept form we have to multiply x-1 by -4 and simplify it then
y=12+(x-1)(-4)
y=12+x*(-4)-1*(-4)
y=12-4x+4
y=-4x+16 - its the result
Step-by-step explanation:
(x+1)squared-squared=2x+1 is always odd because sum of even number and odd number is always odd
Answer:
1, -6
Step-by-step explanation:
Easiest is just to factor
(x+1)(x-6)=0